Monster count : are there 5,8,or 10?Don't be scared and count again!. (New York : Scholastic, 2006)
Count the monsters and the wobbly eyes, which magically disapper as you turn each page
Keywords: Numbers-Juvenile literature; Toy and movable book; Children stories